The Lyapunov exponents for the partitioned-pipe mixer - Stręk, Tomasz (Computer Assisted Methods in Engineering and Science, 2023)
This paper presents a mechanical model of the partitioned-pipe mixer (PPM) in case where pipe of the static mixer rotates with angular periodic velocity. Mixing becomes more efficient if the forcing of fluid mixing process is time periodic. Chaos in duct flows can be achieved by time modulation or by spatial changes along the duct axis. The values of Lyapunov exponents for flow in PPM are calculated.